Sistem Pertahanan Rakyat Semesta Pasca Berlakunya UU PSDN Untuk Pertahanan Negara - SAHABUDDIN, ZAINAL ABIDIN; RAMDANI, EGGY ARMAND (JPAP: Jurnal Penelitian Administrasi Publik, 2020)
Indonesia’s defense system is clearly stated in the Constitution (UUD 1945), namely the The Total People’s Defense and Security (Sistem Pertahanan Rakyat Semesta, Sishanta). Sishanta has a strong philosophical and historical basis in Indonesian culture. Sishanta’s efficacy in dealing with threats has been proven in the nation’s history. The enactment of the National Resource Management Act (PSDN) for National Defense on 26 September 2019 became a new chapter in reviving the concept of Sishanta under a strong legal umbrella. This study examines more deeply the Indonesian culture of defense, how to implement Sishanta after the ratification of the PSDN Law. The research method used is analytical descriptive. The results showed that the Sishanta was the ideal Indonesian defense system in the face of threats. One of Sishanta’s implementing is "Bela Negara" for the society. "Bela Negara" is carried out to produce state defense cadres prepared to become a Reserve Component (Komponen Cadangan) and Supporting Component (Komponen Pendukung) in counteracting threats to Indonesia with the Indonesian National Army (TNI) as the Main Component (Komponen Utama). The "Bela Negara" cadres, in particular, play the role of being the front line in guard Indonesia off nonmilitary and hybrid threats.